Christianity and the Cubiculum : Spiritual Politics and Domestic Space in Late Antique Rome - Sessa, Kristina ca. 20./21. Jh. (Journal of early Christian studies, 2007)
This essay explores the conceptual and material history of a single domestic space, the cubiculum, and its importance for the construction of episcopal authority and private piety in late antique Rome. The cubiculum, a small, typically enclosed room in a Roman house used for a variety of domestic activities (sleep, sex, business and entertainment, poetry writing, magic, and prayer), appears with surprising frequency in both classical and early Christian literature as the most "secret" place within the household, where its occupants might expect to conceal their activities to certain degrees from certain audiences. After a brief delineation of classical, biblical, and patristic conceptualizations of the cubiculum as a secret space as well as its material form in late antiquity, I examine the room's construction as the "martyr's bedroom" in a group of anonymous fifth- and sixth-century Roman passions known as the gesta martyrum. I argue that these Roman texts invited readers to identify their domestic cubicula as legitimate, alternative spaces of spiritual activity in the city, where, like the martyrs, they might practice their own "domesticated" feats of ascetic heroism without direct episcopal supervision. Yet rather than view these narratives as entirely subversive in terms of their spiritual politics, I explain their meaning in light of the rise of a distinctly domestic expression of Christian piety and civic tradition in Rome, one which privileged the household and its members over public, ecclesiastical spaces and figures in the emerging history of Rome's Christianization.